Eksplorasi dan Studi Keragaman Garcinia L. di Sumatera Selatan Berdasarkan Anatomi Kayu - Zulkifli Dahlan; Laila Hanun; Jamila Kemala Sari (Faculty of Mathtmatics and Natural Sciences, 2008)
The research about explanation and variance study to the Garnicia L. In South Sumatera based on wood anatomy has been done on July untul Nopember 2004 at several location in South Sumatera and it was continued in Sitological Laboratory of Herbarium Bogoriense, Bogor. This research aim to identify the variaty of Garcinia L. in South Sumatera based on wood anatomy. It has been done by using descriptive method and survey method (explorative) and using the purposive sampling to secure the research area. The sampling has been done by using incidentally sampling. The macerationally preparation and the wood section preparation were based on The Sass (1959) and Soerodikoesomo (1987) method. The result showed the existence of anatomic characteristic difference primarily and across section.